Comment s’excuser en français et en polonais: étude pragma-sémantique - Grossmann, Francis; Krzyżanowska, Anna (Neophilologica, 2018)
This paper focuses on discursive routines used to express apology in email exchange. We adopt a contrastive (French-Polish) and intercultural approach, integrating apology in the politeness theory. We start from the hypothesis of cognitive grammars (see e.g. Langacker 2008a and 2008b) that apology, even if it includes a shared conceptual core in various languages, presents for each language an original configuration that specifically reorganizes semantic constituents. The results of the research previously conducted by Dziadkiewicz (2007) show that, in the case of apology, the extent of the polite scale in Polish is not the same as in French. The corpus is composed of interpersonal emails (about 200 mails per language) collected in both languages, in professional or private context.